Analisis Timbulan Sampah Pasar Tradisional (Studi Kasus: Pasar Ujungberung, Kota Bandung) - Mochammad Chaerul; Titara Puspita Dewi (Al-Ard: Jurnal Teknik Lingkungan, 2020)
Ujungberung market is one of traditional market in Bandung city having high business transaction and generates a significant solid waste to be managed properly. In order to establish a proper solid waste management, the reliable data on waste generation is crucially required. The paper aims to find the waste generation through performing waste sampling procedure based on Indonesian Standard for 8 days consecutively. There were total 566 stalls available in the market and 85 stalls were selected as respondents for sampling and questionnaire. The results showed that the highest and lowest average of waste quantity were generated by food stall (3.16 kg/day) and tuber stall (0.02 kg/day), respectively. Based on units that may affect the waste quantity, the average daily waste generations are follows: 0,464 kg/stall, 0,109 kg/m2 area of stall, 0,240 kg/employee, 0,047 kg/hour of stall operational. Although the waste composition generated from each stall may vary, the most dominant type of waste predicted to be generated in the market totally were plastic, organic, and paper, respectively. According to the field observation and the questionnaire, most of seller dispose of their waste using plastic bag to the nearest waste storage. The data of waste generation resulted from the study could be used to predict the generation for other traditional market for establishing a better planning of the waste management system.